Creatures of habits? What translators usually do with words - Kenny, Dorothy; Serpa, Talita [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2024)
This paper focuses on some of the methodological and theoretical challenges presented by the investigation of “sanitization” in translated texts through the analysis of semantic prosody. The main hypothesis is that target texts tend to use toned down vocabulary compared with their sources, and that this results in the creation of a “sanitised version of the original”.
Criaturas de hábito? O que os tradutores costumam fazer com as palavras
Keywords: estudos da tradução; higienização; prosódia semântica; sanitisation; semantic prosody; translation studies